Does continuous positive airways pressure treatment improve clinical depression in obstructive sleep apnea? A randomized wait‐list controlled study. Issue 5 (28th December 2020) - Jackson, Melinda L.; Tolson, Julie; Schembri, Rachel; Bartlett, Delwyn; Rayner, Genevieve; Lee, V Vien; Barnes, Maree
Abstract: Background: Obstructive sleep apnea (OSA) is a highly prevalent sleep disorder that is associated with a range of adverse daytime sequelae, including significantly higher rates of clinical depression than is seen in the general community. Improvements in depressive symptoms occur after treatment of the primary sleep disorder, suggesting that comorbid depression might be an intrinsic feature of OSA. However, there are limited data on whether treatment for OSA in patients diagnosed with clinical depression improves mood symptoms meaningfully enough to lead to the remission of the psychiatric diagnosis. Methods: N  = 121 untreated OSA patients were randomized to either continuous positive airway pressure (CPAP) treatment or waitlist control, and depressive symptoms, sleepiness and clinical depression (using a structured clinical interview) were assessed at baseline and 4 months. Linear and logistic regression analyses were conducted, controlling for baseline scores, stratification factors and antidepressant use. Results: Depressive symptoms (odds ratio [OR] = −4.19; 95% confidence interval [CI] = −7.25, −1.13; p  = .008) and sleepiness (OR = −4.71; 95% CI = −6.26, −3.17; p  < .001) were significantly lower at 4 months in the CPAP group compared to waitlist. At 4 months, there was a significant reduction in the proportion of participants in the CPAP group meeting criteria for clinical depression, compared to the waitlist controls (OR = 0.06, 95% CI = 0.01, 0.37; p  = .002). Conclusion: Treatment of OSA may be a novel approach for the management and treatment of clinical depression in those with comorbid sleep disordered breathing. Larger trials of individuals with clinical depression and comorbid OSA are needed.